World on fire. Season two [videorecording (DVD)] - Bowker, Peter, 1958- (PBS, 2023)
"October, 1940. Manchester, England. As valiant Jewish RAF pilot David defends the skies against the Luftwaffe, Harry and Kasia finally arrive home. How will Robina cope with another refugee under roof? When yet another house guest arrives -- Sir James, a civil servant on official business -- he looks set to beguile his host, but will Kasia be charmed as well? Meanwhile, in Berlin, teenager Marga is selected to mother a baby for the Führer, but can her best friend Gertha convince her to reconsider? In North Africa, Stan has found a new enemy in brutal desert conditions while meticulous Officer Rajib leads a team of Indian Sappers in the gravely dangerous task of clearing minefields. And in Paris, Henriette oversees the Resistance escape route" --Container.